(untitled) (Revista Uruguaya de Psicoanálisis, 2000)
The author’s proposal in this theoretic and clinical paper is to discuss the problematic of adolescent patients in risk of suicide. The link between adolescence and death, the immobility as one of the ways the adolescent in risk finds to try to control thethreatened ego cohesión is studied here, focusing also in the acting out which will establish the breakdown between thought and action. At the same time the author rises the question about the place of the analyst in the work with adolescents in risksituations, leading to work many times on the edges of analyzability and challenging him to use his creativity as well.